Can you elaborate on that? Addressing participants' need for cognition in computer-tailored health behavior interventions. Issue 4 (2nd October 2018) - Nikoloudakis, I. A.; Crutzen, R.; Rebar, A. L.; Vandelanotte, C.; Quester, P.; Dry, M.; Skuse, A.; Duncan, M. J.; Short, C. E.
ABSTRACT: Computer-tailored interventions, which deliver health messages adjusted based on characteristics of the message recipient, can effectively improve a range of health behaviours. Typically, the content of the message is tailored to user demographics, health behaviours and social cognitive factors (e.g., intentions, attitudes, self-efficacy, perceived social support) to increase message relevance, and thus the extent to which the message is read, considered and translated into attitude and behaviour change. Some researchers have suggested that the efficacy of computer-tailored interventions may be further enhanced by adapting messages to suit recipients' need for cognition (NFC) – a personality trait describing how individuals tend to process information. However, the likely impact of doing so, especially when tailored in conjunction with other variables, requires further consideration. It is possible that intervention effects may be reduced in some circumstances due to interactions with other variables (e.g., perceived relevance) that also influence information processing. From a practical point of view, it is also necessary to consider how to optimally operationalise and measure NFC if it is to be a useful tailoring variable. This paper aims to facilitate further research in this area by critically examining these issues based on relevant theories and existing evidence.